(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
Chronic liver diseases (CLDs) represent one of the most pressing problems of modern public health, with their global prevalence steadily increasing each year. This group of diseases includes chronic viral hepatitis, alcoholic and non-alcoholic fatty liver disease, autoimmune hepatitis, and liver cirrhosis. Worldwide, chronic liver diseases are among the leading causes of mortality and disability, placing a significant economic burden on healthcare systems. According to data from the World Health Organization, deaths associated with liver diseases occupy one of the leading positions after cardiovascular and oncological diseases. In particular, in developing countries, inadequate sanitary and hygienic conditions, limited access to medical services, and low adherence to healthy lifestyles accelerate the spread of these diseases.